Depth and combined infection is important predictor of lower extremity amputations in hospitalized diabetic foot ulcer patients - Jeong, Eun-Gyo (Korean J Intern Med, 2018)
BACKGROUND/AIMS: As the prevalence of diabetes mellitus and its complications increase rapidly, diabetic foot ulcers (DFUs), which are a major diabetic complication, are expected to increase. For prevention and effective treatment, it is important to understand the clinical course of DFUs. The aim of this study was to investigate the natural course and predictors of amputation in patients with DFUs who required hospitalization METHODS: A total of 209 patients with type 2 diabetes, aged 30 to 85 years, who visited emergency department or needed hospitalization due to DFUs were consecutively enrolled from May 2012 to January 2016, by retrospective medical record review. The main outcome was lower extremity amputation (LEA). RESULTS: Among 192 patients who completed follow-up, 113 patients (58.9%) required LEAs. Compared to patients without amputation, baseline levels of white blood cell counts and C-reactive protein were higher in patients with amputation. In addition, bone and joint involvement was more frequently observed in patients with amputation. Multivariable regression analysis revealed that combined infection (odds ratio [OR], 11.39; 95% confidence interval [CI], 2.55 to 50.93; p = 0.001) and bone or joint involvement (OR, 3.74; 95% CI, 1.10 to 12.70; p = 0.035) were significantly associated with an increased risk of LEA. CONCLUSIONS: The depth of the wound and combined infection of DFU, rather than the extent of the wound, were significant prognostic factors of LEAs in patients with type 2 diabetes.